Beyond Center and Circle Time training for early childhood language development - Isah Cahyani; Lilis Sulistyaningsih; Nunung Sitaresmi; Rohmat Rohmat; Layyina Elwidra Yahya; Intan Karunia Dewi (Universitas Pendidikan Indonesia, 2025)
The Beyond Centers and Circle Time (BCCT) training emerges as a progressive pedagogical intervention, strategically designed to amplify early childhood educators’ capacity in fostering holistic language development among young learners. One of the prevailing challenges educators face in early childhood education (ECE) settings is their limited pedagogical acumen and practical proficiency in employing instructional methodologies that effectively stimulate linguistic growth. This article critically examines the implementation of BCCT training programs for ECE educators and elucidates their implications for children’s language acquisition. The training encompassed a two-day seminar and interactive workshops, engaging 43 educators from 24 ECE institutions across Greater Bandung. The BCCT training at PAUD Bandung Raya began with a comprehensive seminar discussing the importance of literacy for children’s language and cognitive development, early literacy strategies, and the principles and practices of BCCT. Participants then engaged in simulations of eight learning centers—religion, art, music, language, motor skills, science, social studies, and block play—as pedagogical exploration spaces for designing educational play-based activities. The results showed that implementing BCCT successfully constructed a dynamic learning environment, enriched children’s linguistic experiences, strengthened social interactions, and accelerated the expansion of their vocabulary and communication skills. Abstrak Pelatihan Beyond Centers and Circle Time (BCCT) merepresentasikan sebuah intervensi pedagogis progresif yang dirancang secara strategis untuk memperkuat kapasitas profesional pendidik PAUD dalam mengakselerasi perkembangan bahasa anak secara holistik. Salah satu permasalahan krusial yang kerap mengemuka di ranah pendidikan anak usia dini ialah keterbatasan kompetensi pedagogis serta lemahnya keterampilan praktis pendidik dalam menerapkan metodologi instruksional yang efektif dan transformatif dalam merangsang perkembangan linguistik peserta didik. Artikel ini secara kritis mengevaluasi implementasi program pelatihan BCCT bagi pendidik PAUD serta mengkaji dampaknya terhadap akuisisi bahasa anak. Program pelatihan dilaksanakan dalam bentuk seminar dan lokakarya interaktif selama dua hari, melibatkan 43 pendidik dari 24 lembaga PAUD di kawasan Bandung Raya. Pelatihan BCCT di PAUD Bandung Raya diawali dengan seminar komprehensif yang mengulas pentingnya literasi bagi perkembangan bahasa dan kognitif anak, strategi literasi dini, serta prinsip dan praktik BCCT. Peserta kemudian terlibat dalam simulasi delapan sentra pembelajaran agama, seni, musik, bahasa, motorik, sains, sosial, dan balok sebagai ruang eksplorasi pedagogis dalam merancang aktivitas berbasis permainan edukatif. Hasilnya menunjukkan bahwa penerapan BCCT mampu mengkonstruksi lingkungan belajar yang dinamis, memperkaya pengalaman linguistik anak, memperkuat interaksi sosial, serta mengakselerasi perluasan kosakata dan keterampilan komunikasi mereka. Kata Kunci: BCCT; Beyond Centers and Circle Time; pelatihan interaktif; pendidikan anak usia dini; perkembangan bahasa